2011
DOI: 10.1093/bja/aer154
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic analysis of ropivacaine and its metabolite 2′,6′-pipecoloxylidide from pooled data in neonates, infants, and children

Abstract: Ropivacaine and PPX unbound clearance depends on body weight and age. The results support approved dose recommendations of ropivacaine for the paediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 33 publications
3
24
0
1
Order By: Relevance
“…Concentrations of AAG were shown to increase during the course of the surgery and appeared to plateau toward the end of the study period, which is consistent with previous studies . The magnitude of increase in AAG observed in this study is larger (approximately a fourfold median increase) compared to that observed by Booker et al (approximate twofold increase) and in the model developed by Aarons et al As a result of rich sampling at early time points, we observed a minor but consistent reduction in AAG concentrations in the immediate hours after the levobupivacaine, loading dose. This can be best described using an empirical precursor model, inhibiting AAG formation and simultaneously inducing precursor formation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Concentrations of AAG were shown to increase during the course of the surgery and appeared to plateau toward the end of the study period, which is consistent with previous studies . The magnitude of increase in AAG observed in this study is larger (approximately a fourfold median increase) compared to that observed by Booker et al (approximate twofold increase) and in the model developed by Aarons et al As a result of rich sampling at early time points, we observed a minor but consistent reduction in AAG concentrations in the immediate hours after the levobupivacaine, loading dose. This can be best described using an empirical precursor model, inhibiting AAG formation and simultaneously inducing precursor formation.…”
Section: Discussionsupporting
confidence: 91%
“…This was based on a population pharmacokinetic model of unbound levobupivacaine following a caudal injection of levobupivacaine 2 mg/kg given over 30 seconds, in infants undergoing sub‐umbilical surgery . The model was modified to account for time‐dependent changes in levels of AAG following surgery . It allowed the estimation of optimal sampling time points, limiting blood sample volumes in accordance with the WHO guidance .…”
Section: Methodsmentioning
confidence: 99%
“…Mass balance was assumed for total, unbound, and bound drug concentrations in the plasma; an approach that has been widely applied in the target‐mediated drug disposition model for large molecules 30, 31. The model assumptions and parameterizations were different from the model by Aarons et al .,32 where the drug was assumed to exist solely as unbound status right after absorption, and the total drug was then calculated from unbound based on fast equilibrium‐binding.…”
Section: Discussionmentioning
confidence: 99%
“…Using a mass balance principle, this model reproduced the protein binding process of ropivacaine. In previously used approaches, the binding site concentrations (AAG concentrations) did not affect free ropivacaine pharmacokinetics and were therefore unable to reproduce the decrease in free ropivacaine over time (Figure ). Our model accurately described the temporal changes in the unbound ropivacaine fraction (Figures , and ).…”
Section: Discussionmentioning
confidence: 99%
“…A prior distribution based on the work of Aarons et al . was introduced for K d . This prior followed a normal distribution with mean equal to 0.58 μ m and an SD of 0.05.…”
Section: Methodsmentioning
confidence: 99%